2004
DOI: 10.4314/eamj.v81i1.8789
|View full text |Cite
|
Sign up to set email alerts
|

Oral habits among 7-10 year-old school children in Ibadan, Nigeria

Abstract: None of the children examined had gone for routine dental check-ups before except for the 62(12.6%) who had previous dental consultations due to toothaches. Conclusion: Oral habits especially digit sucking needing management was revealed by this study and none of them had been to a dentist for help. This suggests that there is need to intensify oral health education in our environment, targeted at both parents and school children to enable them benefit from interceptive orthodontic care which has numerous adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…Overall, almost half of the patients seen indulged in oral habits. Studies[ 17 18 19 ] of the general populace have reported a prevalence of oral habits ranging from 9.9 to 34.1% in Nigerian children of varied ages with digit sucking being reported as the most common oral habit. Digit sucking was also the most prevalent oral habit in this population (15.8%) and is a major cause of increased overjet and anterior open bite which was observed in 44.6% and 14.8% of the population, respectively, thus habit breakers were the most recommended treatment option for this population (20.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, almost half of the patients seen indulged in oral habits. Studies[ 17 18 19 ] of the general populace have reported a prevalence of oral habits ranging from 9.9 to 34.1% in Nigerian children of varied ages with digit sucking being reported as the most common oral habit. Digit sucking was also the most prevalent oral habit in this population (15.8%) and is a major cause of increased overjet and anterior open bite which was observed in 44.6% and 14.8% of the population, respectively, thus habit breakers were the most recommended treatment option for this population (20.7%).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Just like in other countries, the philosophy of early orthodontic treatment and preventive and interceptive orthodontics is advocated in Nigeria. 13,[16][17][18][19][20][21] This treatment philosophy is more needful considering the high poverty level in a developing economy like Nigeria and the high cost of comprehensive orthodontic treatment. According to Bishara et al, 1 an understanding of the anteroposterior changes that occur in the occlusion between the deciduous and permanent dentition is crucial for the clinician involved in early orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This percentage makes up a significant amount when compared to other researches for example a study conducted by Onyeaso in 2004 reported only about 1.2% of children with lip sucking. 6 The results obtained also show that the highest numbers of lip suckers were found in the 9-years-old children (32%), followed by 8 year olds and 6 year olds both representing 25% of the total sample. The least percentage is represented by 7 year olds with 18 %.…”
Section: Discussionmentioning
confidence: 64%